In vitro and in vivo characterisation of the metabolism and disposition of suvorexant in humans. (2nd October 2016) - Cui, Donghui; Cabalu, Tamara; Yee, Ka Lai; Small, James; Li, Xiaodong; Liu, Bo; Maciolek, Cheri; Smith, Sheri; Liu, Wen; McCrea, Jacqueline B.; Prueksaritanont, Thomayant
Abstract: 1. Suvorexant (MK-4305, Belsomra®) is a first-in-class dual orexin receptor antagonist approved in the USA and Japan for the treatment of insomnia. The current studies describe suvorexant's absorption, disposition and potential for CYP-mediated drug interactions in humans. 2. Following single oral administration of [ 14 C]suvorexant to healthy human subjects, 90% of the radioactivity was recovered (66% in faeces, 23% in urine), primarily as oxidative metabolites. 3. In plasma, suvorexant and M9 were predominant, accounting for 30 and 37% of the total radioactivity, respectively. Metabolite M17 became more prominent (approaching 10%) following multiple daily doses of unlabelled suvorexant. M9 and M17 are not expected to contribute to the pharmacological activity of suvorexant due to reduced orexin receptor binding affinity and limited brain penetration. 4. CYP3A was determined to be the predominant enzyme mediating suvorexant oxidation. In vitro, suvorexant demonstrated reversible inhibition of CYP3A4 and 2C19 (IC50 ∼ 4–5 μM), and weak time-dependent inhibition of CYP3A4 ( K I  = 12 μM, k inact  = 0.14 min −1 ). Suvorexant was also a weak inducer of CYP3A4, 1A2 and 2B6. Given the low plasma concentrations at clinical doses, suvorexant was not anticipated to cause significant drug interactions via inhibition and/or induction of major CYPs in vivo .